The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Design Computing and Cognition '14 2015
DOI: 10.1007/978-3-319-14956-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Eye Tracking and Think-Aloud Methods in Engineering Design Research

Abstract: In order to understand the engineers' behavior while designing it needs to be revealed how the designer perceives function-shape-relations of a technical system. Eye tracking is a adequate method to observe the proceedings of the human analyzing technical systems. However, further information for concluding on the designer's perception is needed. Well-established methods in order to elicit further implicit and tacit knowledge are think aloud approaches. The combination thinkaloud and eye tracking is not yet ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…In Ruckpaul et al . (2014), two different think-aloud methods, that is concurrent and retrospective, are analyzed for the evaluation of a drawing of a technical system – actually, participants are asked to judge if the system works correctly. The findings show that the two methods, while performing differently in terms of the extracted content of the verbalization, do not show significant variations in terms of ET measures.…”
Section: Studies Of Design Processes and Designers' Cognition With Bimentioning
confidence: 99%
“…In Ruckpaul et al . (2014), two different think-aloud methods, that is concurrent and retrospective, are analyzed for the evaluation of a drawing of a technical system – actually, participants are asked to judge if the system works correctly. The findings show that the two methods, while performing differently in terms of the extracted content of the verbalization, do not show significant variations in terms of ET measures.…”
Section: Studies Of Design Processes and Designers' Cognition With Bimentioning
confidence: 99%
“…Previously, the combination of thinking aloud and eye tracking was observed in detail (Ruckpaul et al, 2014a), and results showed that the former did not have significant influence on the latter. Here, we may consider the dynamics of shifting viewpoints and verbal features as independent but connected when a product is examined by the user.…”
Section: Dynamics Of Shifting Viewpoints and Verbal Featuresmentioning
confidence: 92%
“…Die anschließenden retrospektiven Think-Aloud Interviews (vgl. Van Gog et al 2005;Ruckpaul et al 2015;Van Den Haak et al 2003;Whalley und Kasto 2014) wurden aufgezeichnet und analysiert. Sie bilden die Grundlage für die später formalisierte Beschreibung der Vorgehensweisen.…”
Section: Aufzeichnungunclassified